Interoperability for Online Learning platforms and Quality in Higher Education (Web of Teachers: Inderscience Research, 2023)
This research is an extended works that presents the broad multidimensional reference model for E- Learning standard as the main result. The importance and task of interoperability as well as quality development and their relationship which will be defined and analyzed in King Khalid University, Particularly in E- Learning where association and interdependence is apparent. This research is based primarily on secondary data provided by E- Learning Deanship and E- Learning Experts of King Khalid University. Open Ended questionnaire is designed to collect data from E- Learning experts and E- Learning website is evaluated with the focus of E- Learning reference model. In this research Interoperability and Quality Development relationship will be defined with its extent of presence in King Khalid University. Categories of E- Learning standards with its dimensions will be defined too with respect to King Khalid University. After a short introduction of the relevant E- Learning standardization committees and initiative (ISO/IEC JTCISC 36, IEEE LTSC, IMS and ADI) their published standards and specification are used to evaluate the Reference Model for E- Learning Standards particularly for King Khalid University. As an effect it can be stated that the reference model is covering all kinds of E- Learning standards and that is applicable and appropriate for their differentiation and categorization prevailing in King Khalid University. In ending, a revelation of challenges for potential for E- Learning standardization is outline for the prospect. This study of Interoperability of Reference Model for E- Learning and Quality Development can then be used on any system, not only for information technology system. This research will show the method of establishing the relationship of quality model and E- Learning reference model for educational organization.